Oncologic outcome of multimodality treatment for sinonasal malignancies: An 18-year experience - Chen, Meng-Yu; Wen, Xin; Wei, Yi; Chen, Lin; Huang, Zi-Xuan; Lu, Tong; Zheng, Nian-Zhen; Li, Jian; Wen, Wei-Ping; Wen, Yi-Hui (Frontiers in Oncology, 2022)
Purpose The aim of this study was to retrospectively evaluate the oncologic outcomes of sinonasal malignancies (SNMs) of various histologic subtypes and investigate the impact of multimodality treatment on prognosis of SNM. Methods SNM patients treated with curative-intent surgery from 2000 to 2018 were included. The primary outcomes were overall survival (OS). Survival was then assessed through Cox proportional hazards models. Results Three hundred and three patients were eligible for the analysis. The 5-year OS and event-free survival (EFS) were 61.0% (95% CI: 55.4%–67.1%) and 46.2% (95% CI: 40.4%–52.7%). The 5-year OS was the worst for malignant melanoma and the best for adenocarcinoma. Patients who received surgery had better OS than those who only received radiotherapy and/or chemotherapy. Endoscopic surgery had better OS than the open approach (p < 0.05). Microscopically margin-negative resection (R0 resection) significantly benefited OS and EFS (p < 0.001). No significant difference in OS was observed between patients who received macroscopic complete resection (R1 resection) followed by adjuvant therapy and patients who received R0 resection. Older age (HR = 1.02, p = 0.02), R1 resection (HR = 1.99, p = 0.02), sinonasal surgical history of more than 3 months before diagnosis (HR = 2.77, p = 0.007), and radiotherapy history (HR = 3, p = 0.006) are risk factors for worse EFS. Conclusions Curative-intent surgery is irreplaceable in the treatment of SNM. The endoscopic approach is an effective alternative to the open approach. EFS is worse among patients with older age, R1 resection, sinonasal surgical history of more than 3 months before diagnosis, and radiotherapy history.